DAMPAK PENGEMBANGAN SHALE GAS AMERIKA SERIKAT TERHADAP EKSPOR BATUBARA INDONESIA KE AMERIKA SERIKAT - Ariesanti, Hanny; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research discusses about the implication of shale gas development to Indonesia coal export to United States. United States is one of the biggest energy consumption states. As a superpower state that has second lead in energy consumption, United States has to keep save its energy security. United States begin to develop alternative energy, such as shale gas resources. Shale gas development reach the successes which shale gas has been consumed for a half of total energy consumption in the United States lately. United States has a lot of shale gas resources in the country that not only decrease the gas prices but also makes a substitution of energy in US. The substitution does implication to other energy resources such as coal that has been used in United States for several years.This research is based on librarian research like book, relevant, journal, newspaper and internet.In this research, the writer uses qualitative research method.Using a level analysis of state, the used perspective is structuralism perspective to understand the implication of shale gas development.Indonesia is the biggest coal exporter country in the world. The coal is imported by several countries include the United States. However, since there was shale gas development several years ago, the energy of coal has been substitute in the United States that has an impact to Indonesia coal export into the United States. The United States consumption and production of coal has been decreased because of the subtitution which impact to coal prices and coal demand in the United States.Keyword: Energy, Shale Gas, Impact, Energy Subtitution, Coal, Export